Diagnóstico e tratamento de púrpura trombocitopenia imune: uma revisão literária. - Silva, Francykléa Lourenço (2014)
The immune thrombocytopenia purpura is a condition characterized by the decreased number of central and peripheral platelets. Is considered benign and self - limiting in most cases and can be classified according to the age , diagnosis, severity and duration of the illness. The clinical appearance is distinguished by bleeding in the presence of thrombocytopenia, the most common being petechiae, ecchymosis, epistaxis, gingival bleeding and menorrhagia. The diagnosis continues t o be made by ruling out. In this study, a literature review was done in order to analyze the latest findings of the literature review and research findings on the disease made in Brazil. During this work achievement it was observed that there is still contentious issues on both the diagnosis and the treatment of the condition and there is a need for studies to define the actual situation of the disease in our country, the creation of a database for the development of guidelines that fit the national pro file of the disease and thus have a diagnosis, treatment and effective monitoring and appropriate for individuals with this disease.